Perbandingan Indeks Massa Tubuh Dan Metabolisme Lemak Pada Wanita Menopause Di Rumah Sakit Umum Royal Prima Medan - Amansyah, Adek; Putri, Azkya Aulia; Suandy , Suandy (Syntax Corporation, 2025)
Menopause is a natural phase experienced by every woman and is characterized by the cessation of reproductive function due to a decrease in the hormones estrogen and progesterone. This condition not only affects the reproductive system but also impacts changes in fat metabolism and an increase in Body Mass Index (BMI), potentially increasing the risk of metabolic and cardiovascular disorders in postmenopausal women. This study aims to compare body mass index and fat metabolism in menopausal women. This study is an experimental study with a quasi-experimental design. The study was conducted at Royal Prima General Hospital, Medan. The study population consisted of all postmenopausal women undergoing medical examinations at Royal Prima General Hospital, Medan. A sample size of 40 individuals was divided into two groups. Sampling was conducted using purposive sampling. Data analysis was performed using univariate and bivariate analyses using the Independent Sample T-Test at a 95% confidence level (α=0.05). The results showed that most respondents were >50 years old, predominantly had overweight BMI categories, and presented lipid profiles categorized as borderline–high to high. Bivariate analysis revealed no significant differences between the two groups for all examined variables, including BMI (p = 0.675), total cholesterol (p = 0.745), LDL (p = 0.525), HDL (p = 0.968), and triglycerides (p = 0.914). Although statistically insignificant, the distribution of data indicated a tendency for increased total cholesterol, LDL, and triglyceride levels in the group with menopause duration >5 years, suggesting metabolic changes associated with prolonged menopausal status.